AhR Activation Transcriptionally Induces Anti-Microbial Peptide Alpha-Defensin 1 Leading to Reversal of Gut Microbiota Dysbiosis and Colitis - Manikandan Palrasu; Khadija Kakar; Amarnath Marudamuthu; Hamida Hamida; Shruthi Thada; Yin Zhong; Shanieka Staley; Philip Brandon Busbee; Jie Li; Monica Garcia-Buitrago; Mitzi Nagarkatti; Prakash Nagarkatti (Gut Microbes)
Alpha-defensin 1 is a small antimicrobial peptide that acts as the first line of defense against pathogens. It is induced following microbial cues and inflammatory signals in neutrophils and Paneth cells in the small intestine, which suggests that it plays a role in microbial homeostasis in the gut. The gut microbial products also serve as ligands for the aryl hydrocarbon receptor (AhR), an environmental sensor. In the current study, we investigated if there is any crosstalk between AhR and alpha-defensin 1. Interestingly, we found a positive correlation between AhR and alpha-defensin 1 protein levels in ileal tissues from active Crohn’s’ (CD) patients and epithelial cells (IECs) from multiple models of murine colitis. In vitro downregulation of AhR led to inhibition of α-defensin 1, while activation of AhR induced α-defensin 1 in IECs. AhR directly targeted the dioxin response element 3 (DRE3) region on the α-defensin 1 promoter in IECs. AhR-mediated induction of α-defensin 1 in colitis mice reversed the gut microbial dysbiosis and alleviated colitis. Our data identify a novel signaling pathway in which AhR acts as a transcription factor for α-defensin 1, leading to regulation of homeostasis between gut microbiota, intestinal mucosa, and mucosal immunity.